Phosphinous Acid‐Assisted Hydration of Nitriles: Understanding the Controversial Reactivity of Osmium and Ruthenium Catalysts. Issue 60 (9th October 2017) - González‐Fernández, Rebeca; Crochet, Pascale; Cadierno, Victorio; Menéndez, M. Isabel; López, Ramón
Abstract: The synthesis and catalytic behavior of the osmium(II) complexes [OsCl2 ( η 6 ‐ p ‐cymene)(PR2 OH)] [R=Me (2 a ), Ph (2 b ), OMe (2 c ), OPh (2 d )] in nitrile hydration reactions is presented. Among them, the best catalytic results were obtained with the phosphinous acid derivative [OsCl2 ( η 6 ‐ p ‐cymene)(PMe2 OH)] (2 a ), which selectively provided the desired primary amides in excellent yields and short times at 80 °C, employing directly water as solvent, and without the assistance of any basic additive (TOF values up to 200 h −1 ). The process was successful with aromatic, heteroaromatic, aliphatic, and α, β‐unsaturated organonitriles, and showed a high functional group tolerance. Indeed, complex 2 a represents the most active and versatile osmium‐based catalyst for the hydration of nitriles reported so far in the literature. In addition, it exhibits a catalytic performance similar to that of its ruthenium analogue [RuCl2 ( η 6 ‐ p ‐cymene)(PMe2 OH)] (4 ). However, when compared to 4, the osmium complex 2 a turned out to be faster in the hydration of less‐reactive aliphatic nitriles, whereas the opposite trend was generally observed with aromatic substrates. DFT calculations suggest that these differences in reactivity are mainly related to the ring strain associated with the key intermediate in the catalytic cycle, that is, a five‐membered metallacyclic species generated by intramolecular addition of the hydroxyl group of the phosphinous acid ligand to the metal‐coordinated nitrile. Abstract : Osy Osy Osy !: An efficient osmium‐based catalyst for the hydration of nitriles, namely [OsCl2 ( η 6 ‐ p ‐cymene)(PMe2 OH)], able to operate at 80 °C in pure water and under neutral conditions, is presented. DFT calculations intended to understand the differences in catalytic activities observed between this complex and its ruthenium analogue are also described.